The Use of Voice Recorder Aplication to Improve Students' Speaking Skill - Diyansyah, Harno (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
English is an international language,many science books and economic busines market in this world use english as formal language to connect each other.But in fact, learning English as second language still became a problem for indonesian students. It is might lack of creativity between teacher and learner in exploit new tings around us every day. The students problem are so variety,start form; lack of media,lack of self confiden and many more. Basically, there are four skills required in English teaching learning program. They are reading, speaking, listening and writing. Base on those skill, speaking is one of the most important skill in language learning. By speaking, we can convey information and ideas, and maintain social relationship by communicating with others.By speaking people make interaction between individua1 and community. The writer tried to use voice recorder aplication as media to improve student in speaking skill and used picture as media to control student focuse during their spek ,the reason is because every students in indonesia especially in west java have phone cell. their phone cell are so variety with the famous operational system (OS)in their phone,they are; Iphone,Android,Blackberr, Microsoft. Voice recorder are comon feature in every singlephone and many variety of voice model.